Prevalence of Intestinal Parasitic Infection and Its Associated Factors Among School Children in Two Primary Schools in Harbu Town, North East Ethiopia: Cross-Sectional Study - Gebretsadik D; Tesfaye M; Adamu A; Zewde G (Dove Medical Press, 2020)
Daniel Gebretsadik,1 Melkam Tesfaye,1 Aderaw Adamu,1 Gashaw Zewde2 1Department of Medical Laboratory Science, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 2Ataye District Hospital, Ataye, North Shoa, EthiopiaCorrespondence: Daniel Gebretsadik Tel +251 910541073Email gebretsadikd@gmail.comBackground: Intestinal parasitic infections (IPIs) are major health problems in many developing countries. School children between the ages of 5 and 15 years suffer the highest infection rate and parasitic burden that are attributed to poor sanitation and hygiene. In Ethiopia, the prevalence of IPIs among school children is high (ranging from 66.7% to 83.8%).Methods: School-based cross-sectional study was conducted in two primary schools at Harbu Town, Northeast Ethiopia from February to May, 2018. Systematic random sampling technique was employed to select study participants from the two school compounds. The sample size was determined by a single population proportion statistical formula and the minimum numbers of study participants defined were 400 school children. Socio-demographic and risk factor-related information were collected using structured questionnaire. Data about detection and identification of intestinal parasites were obtained from laboratory examination of stool specimen by using wet mount and formol-ether concentration techniques. Stool specimen from each study participant was collected using clean, properly labeled and leak-proof stool cup. The data were processed and analyzed using SPSS version 20 software.Results: Out of a total of 400 study participants, 86 (21.5%) were found with one or more IPIs. Six different types of intestinal parasites were identified, Entamoeba histolytica was the most 33 (8.3%) detected parasite followed by Hymenolopis nana 19 (4.8%) and Schistosoma mansoni 19 (4.8%). The least identified parasite was Giardia lamblia, detected only from four study participants. Male study participants showed 2.42 times risk (AOR = 2.42, 95% CI = 1.25– 4.7, P = 0.009) of acquiring parasitic infection than female. Presence of water body near to home and having contact with water bodies showed 7.64 (AOR= 7.64, 95% CI= 3.3– 17.8, P= 0.000) and 4.6 (AOR=4.6, 95% CI: 2.04– 10.57, P= 0.000) times risk of infection with parasitic infection among school children, respectively.Conclusion: IPIs were highly prevalent health problem among the two primary school children in Harbu Town. Sex, availability of water bodies near to house and contact with water bodies were having significant association with the prevalence of IPIs.Keywords: intestinal parasites, Harbu, school children, Ethiopia